Inovasi Business Room untuk Meningkatkan Kompetensi Kewirausahaan Siswa di SMK - Anis Wiji Lestari; Indra Hastuti; Agus Suyatno (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Vocational education at SMK Citra Medika Sragen faces significant challenges in enhancing students' entrepreneurial competence to ensure they remain competitive and relevant to the demands of a dynamic job market. Currently, the implementation of the Business Room innovation often encounters serious obstacles, such as limited supporting facilities and a sub-optimal role of teachers in guiding students. This study aims to analyze the management strategy of teacher career development within the Business Room innovation and to describe the teachers' roles, supporting and inhibiting factors, and their impact on students' entrepreneurial competence. This research employs a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation, which were then analyzed using an interactive model with triangulation techniques to ensure data validity. The research findings indicate that the teacher career development management strategy is structured through needs-based training planning, the application of the Project-Based Learning (PjBL) method, and routine evaluations that are adaptive to market trends. Teachers have successfully transformed into reliable business facilitators and mentors, supported by adequate Teaching Factory facilities. The integration of teacher career development strategies has proven crucial in creating an effective learning ecosystem. Overall, this management strategy has a significant impact on improving students' knowledge, skills, and entrepreneurial attitudes. The implications of this study emphasize the importance of strengthening the legality of innovation products and expanding industrial partnership networks to ensure the sustainability of the learning program in the future.